PENGARUH MANAJEMEN KINERJA TERHADAP PERILAKU KARYAWAN PADA PT. POS INDONESIA RANTAU PRAPAT - MAJU SIREGAR (JURNAL ILMIAH KOHESI, 2021)
The research aims to determine the influence of performance management on employee behavior at PT. POS IndonesiaRantau Prapat. This study was conducted from December 01, 2018 to May 21, 2019. The number of samples in this study asmany as 60 people. Variables in the study consisted of free variables namely performance management (X), while boundvariables were employee behavior (Y). Data analysis is done with a simple regression test. Based on the method applied bythe authors, this study obtained a partial hypothesis test, on performance management variables have a significant influenceof 0.00 < 0.05 (value degree of freedom) on employee behavior. In addition, the beta value showed a result of 0.529 whichmeans it has a positive and significant effect. Based on the coefficient of determination test can be seen the R-Square valueof 0.248. This means that a 24.8% variation in the value of employee behavior can be explained by the role of performancemanagement. So it can be concluded that performance management affects employee behavior by 24.8% and the remaining75.2% is influenced by other variables such as incentives, training, and organizational environment.